Blue Economy: The Role of Attitudes and Behaviors in Occupational Health and Safety - Yuli Budiati; Hardhani Widiastuti; MM Shinta Pratiwi; Indarto Indarto; Rebecca R Maquilling; Joel B. Tan; Rosalia T Gabronino (Integrated Journal of Business and Economics (IJBE), 2025)
This research examines the challenges of Mina MSMEs on the coast of Demak, Central Java, which rely on marine resources but are vulnerable to exploitation. The purpose of this study is to assess how attitudes and behavior affect productivity at work, so that a blue economy can be realised. This study was conducted using a survey method with a population of fish processors MSMEs in Demak Regency, Central Java, Indonesia, using a census by collecting 48 respondents. Partial least square was the technique utilized for data analysis. The result indicate that attitudes and behaviors related to OHS have a significant influence on productivity and the blue economy, where productivity does not mediate the influence of OHS attitudes but mediates the influence of OHS behavior on the blue economy. The implication is that the government should adopt a comprehensive approach towards MSMEs for the development of a culture of occupational safety and health through socialisation, training, monitoring, and enforcement of safety regulations as an effort to prevent and minimize workplace accidents, thereby fostering awareness of the importance of safety and health in the workplace.